Genome-wide analysis of heat shock transcription factor families in rice and Arabidopsis - Guo, J.; Wu, J.; Ji, Q.; Wang, C.; Luo, L.; Yuan, Y.; Wang, Y.; Wang, Y.
The heat shock transcription factors (HSFs)are the major heat shock factors regulating the heat stress response. They participate in regulating the expression of heat shock proteins (HSPs), which are critical in the protection against stress damage and many other important biological processes. Study of the HSF gene family is important for understanding the mechanism by which plants respond to stress. The completed genome sequences of rice (Oryza sativa)and Arabidopsis (Arabidopsis thaliana)constitute a valuable resource for comparative genomic analysis, as they are representatives of the two major evolutionary lineages within the angiosperms: the monocotyledons and the dicotyledons. The identification of phylogenetic relationships among HSF proteins in these species is a fundamental step to unravel the functionality of new and yet uncharacterized genes belonging to this family.In this study, the full complement of HSF genes in rice and Arabidopsis has probably been identified through the genome-wide scan. Phylogenetic analyses resulted in the identification of three major clusters of orthologous genes that contain members belonging to both species, which must have been represented in their common ancestor before the taxonomic splitting of the angiosperms. Further analysis of the phylogenetic tree reveals a possible dicot specific gene group. We also identified nine pairs of paralogs, as evidence for studies on the evolution history of rice HSF family and rice genome evolution. Expression data analysis indicates that HSF proteins are widely expressed in plants. These results provide a solid base for future functional genomic studies of the HSF gene family in rice and Arabidopsis.
Keywords: HEAT STRESS TRANSCRIPTION FACTOR; ORYZA SATIVA (RICE); ARABIDOPSIS THALIANA; PHYLOGENETIC ANALYSIS